Theoretical concepts and models of translation: essence, functions, types - Kuzar* Ж.Н.; Kuldeeva Г.И. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
The article provides a brief comparative review of foreign language translators on the essence of translation, with the main emphasis on the translation process itself with reference to various translation description models. Traditional and modern views on the concept of translation models are analyzed. It is stated that the attention to translation practice after the second half of the ХХ century has intensified worldwide for three main reasons: historical, theoretical, and pragmatic. The authors of the article made an attempt to find the most optimal models of translation, using those that give a maximum approximation to the source text. The study focuses on written translation. The main concepts discussed in the framework of this publication are «equivalence», «textual equivalence», «translation model». The authors hold the view that for terminological differences there are definite differences in theoretical orientation and methodological approaches. On this basis, it is possible to formulate a number of fundamentally important provisions, based on which it is necessary to make conclusions about the methodological and epistemic possibilities of translation.